Minimally Invasive Versus Open Spinal Fusion Surgery for Spondylolisthesis Treatment - Shahzad Waqas Munazzam; Vikramaditya Rai; Qazi Adam Asfandyar; Shandana Khan; Cara Mohammed (Journal of Orthopaedic Case Reports)
Background: In recent years, there has been a growing utilization of minimally invasive (MI) techniques, which provide the potential advantages of minimizing surgical stress, post-operative pain, and hospitalization duration. Nevertheless, the existing body of literature primarily comprises of studies conducted at a single medical site, which are of low quality and lack a comprehensive analysis of treatment techniques exclusively focused on spondylolisthesis. We conducted this systematic review and meta-analysis to compare minimally invasive surgery (MIS) and open surgery (OS) spinal fusion outcomes for the treatment of spondylolisthesis. OS spinal fusion is an interventional option for patients with spinal illness who have not had success with non-surgical treatments. Materials and Methods: This systematic review of the literature regarding MI and OS spinal fusion for spondylolisthesis treatment was performed using the preferred reporting items for systematic reviews and meta-analysis guidelines for article identification, screening, eligibility, and inclusion. Electronic literature search of Medline/PubMed, Cochrane Library, and Google Scholar databases yielded 1078 articles. These articles were screened against established criteria for inclusion into this study. Results: A total of eight retrospective and four prospective articles with a total of 3354 patients were found. Reported spondylolisthesis grades were I and II only. Overall, MI was associated with lower operative time (mean difference [MD], −6.44 min; 95% confidence interval [CI], −45.57–32.71; P = 0.0001) and shorter length of hospital stay (MD, −0.49 days; 95% CI, −0.58 to −0.40; P = 0.000). There was no significant difference overall between MIS and OS in terms of functional or pain outcomes. Rates of complications were not significantly different between the MI group and the OS group, though overall 75 and 153 complications were observed in MI group and OS group. Conclusion: Available data indicate that MI spinal fusion is a secure and efficient method for managing Grade I and Grade II spondylolisthesis. Furthermore, whereas prospective trials establish a connection between MI and improved functional outcomes, it is necessary to conduct longer-term and randomized trials to confirm any correlation identified in this study.